Power Factor Improvement of a Three Phase Rectifier by Boost Regulator (Journal of Electrical Engineering, 2011)
In this paper, a Boost regulator based three phase rectifier for unity power factor is analyzed and described. To implement the proposed model requires a single switch Boost regulator between the three phase diode rectifier and load. Pulse width modulation (PWM) technique is used to control of Boost regulator. Power factor improvement is accomplished by using PWM technique and passive LC high frequency harmonics filters. This paper shows that when harmonics filter is attached with input LC filter then input current becomes sinusoidal input current and power factor improves notably. By reduction of undesirable harmonics this model is able to remove possibility of unwanted resonance. The performance of the rectifier improved than that reported in previous works through Boost preregulator. Index Terms: Three phase rectifier input current; Boost preregulator; harmonics filter. J. Elec. Engg., Instn. Engrs., Bangladesh, 36(II), December 2009: 22-27